Religious Moderation In The Framework Of Malay Islam - M. Zakariya Al Ansori; Haris Riadi; Raihana Aulia Sukhairani (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aims to examine the concept and practice of religious moderation within the framework of Malay Islam and its relevance in maintaining social harmony in the modern era. This research employs a qualitative approach using library research, drawing on various scholarly sources such as journals, books, and related documents. The findings reveal that religious moderation in Malay society is reflected through the integration of Islamic values with local culture, based on the principle “custom is founded upon Islamic law, and Islamic law is founded upon the Qur’an.” Values such as tolerance, balance, justice, and deliberation serve as the foundation for building harmonious social life. However, religious moderation also faces challenges in the modern era, including globalization, digital media influence, and the emergence of extreme religious ideologies. Therefore, strengthening strategies are needed through education, the role of religious and traditional leaders, as well as the wise use of digital media. This study concludes that religious moderation within the Malay Islamic framework plays a significant role in creating a tolerant, inclusive, and civilized society.